Pemanfaatan Aplikasi Web sebagai Media Pembelajaran Daring untuk PKBM Bhakti Asih: The Implementation of Web Applications as an Innovative Learning Medium for PKBM Bhakti Asih - Syarif, Achmad; Prasetya, Rizky Eka; Alam, Sukma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The collaborating organization for this community service initiative is PKBM Bhakti Asih Ciledug, situated in Jalan Raden Fatah No. 7 RT 03 RW 10, West Sudimara Village, Ciledug District, Tangerang City, Banten Province 15151. The present issue with the partner is the suboptimal exploitation and implementation of Information and Communication Technology (ICT), particularly in relation to teaching and learning activities. PKBM enrolls students from various backgrounds, resulting in a wide range of perspectives and interpretations of the content. Therefore, it is necessary to have learning materials that can enable individuals to review and revisit their learning at any given time. Web applications offer a potential answer to this issue, since they can serve as an online learning platform that is accessible at any given moment. Students are trained in the use of this online application through in-person instruction at the ICT lab of Budi Luhur University. Based on the findings of the activity assessment questionnaire, over 90% of participants expressed that this activity was valuable, comprehensible, impactful, and met their expectations. Therefore, it may be inferred that this activity has the potential to offer resolutions to the challenges encountered by partners.